Analysing barriers to supplier quality management via interpretive structural modelling: the case of Saudi industry. Issue 4 (2016) - Mukhtar, Hassan; Schiffauerova, Andrea
A well-organised supply chain network increases the efficiency of the supplier selection and improves quality of service. However, certain barriers to suppliers' quality management prevent companies from achieving these gains. The aim of this study is to identify important barriers that affect suppliers' quality management and to determine the contextual relationships between them using interpretative structural modelling approach. Based on literature review seven important barriers to quality management were identified at the supplier level and a graphical approach was then used to classify these barriers into multiple categories. Experts' opinion from Saudi industry was sought to develop structured self-intersection matrix and reachability matrix, which are used to identify binary relationship among these barriers. The study provides new insights into understanding of the critical factors hindering successful supply chain management.